Investigations into variations in local cationic environment in layered oxide series InGaO3(ZnO)(m) (m=1-4) - Narendranath, Soumya B.; Yadav, Ashok Kumar; Ajithkumar, Thalasseril G.; Bhattacharyya, Dibyendu; Jha, Shambhu Nath; Dey, Krishna K.; Raja, Thirumalaiswamy; Devi, R. Nandini (Dalton Transactions, 2014)
Layered oxides of the series InGaO3(ZnO)(m) (m = 1-4) are interesting due to their structural anisotropy. Here, we report a comprehensive study of their structural details, focusing on the local cationic environment in bulk powder samples by MASNMR and EXAFS, which is hitherto not attempted. It is found that the Ga geometry varies gradually from pure pentacoordinated to a mixture of penta and tetracoordinated with increasing amounts of tetracoordination as we move across the series, contrary to previous reports suggesting exclusively trigonal bipyramidal coordination in all the compounds. A similar observation is also made in the case of Zn and structural evolution involving the dissolution of Ga in a ZnO4 tetrahedral network in a sandwich layer can be discerned, as the insulating ZnO layer size increases.

Photocatalytic H-2 evolution from water-methanol system by anisotropic InFeO3(ZnO)(m) oxides without cocatalyst in visible light - Narendranath, Soumya B.; Yadav, Ashok Kumar; Bhattacharyya, Dibyendu; Jha, Shambhu Nath; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2014)
InFeO3(ZnO)(m), series of oxides are found to give unprecedented H-2 evolution from water-methanol mixtures without using any cocatalysts. This family of compounds has an anisotropically layered structure in which Zn/FeOn polyhedra are sandwiched between InO6 octahedral layers. Local structure characterization by X-ray absorption spectroscopy reveals that Zn coordination changes from pentacoordinated to tetrahedral geometry across the series, whereas Fe geometry remains trigonal bipyramidal in all the compounds. This peculiar structure is conducive for a spatial separation of photogenerated charges reducing recombination losses. Band gap energies calculated from absorption spectra indicate potential visible light activity, and this may be due to the orbital mixing of Fe 3d and O 2p as revealed by pre-edge features of X-ray absorption spectra. Band positions are also advantageously placed for a visible light H-2 generation and is indeed found to be the case in methanol-assisted water splitting with standardized hydrogen evolution of similar to 19.5 mmol g(-1) h(-1) for all the catalysts.
Keywords: anisotropic structure; H-2 evolution; InFeO3(ZnO)(m); layered oxide; photocatalytic water splitting